Processes of wet deposition. [Atmospheric deposition of nitrogen compounds in Danish coastal waters]. Processer for vaaddeposition - "Asman, W A.H."; "Klint Jensen, P [Danmarks Miljoeundersoegelser, Roskilde (Denmark)]" (Copenhagen (Denmark); Miljoestyrelsen, 1993)
Estimates show, that atmospheric deposition of nitrogen components contributes one third of the total nitrogen load in Danish coastal waters. This report describes wet deposition processes and the atmospheric transport models that have been developed to describe these processes. Calculations suggest that ammonia, ammonium in aerosols, nitric acid, and nitrate in aerosols are responsible for almost all nitrogen found in precipitation. Models have been developed to describe the uptake of chemical components within clouds and removal of components by falling raindrops under the cloud base. The latter is used to calculate below-cloud scavenging coefficients for soluble gases (ammonia, nitric acid, hydrogen peroxide and hydrochloric acid). A general model has been developed which is able to describe both reactions and transport between phases. An increase in the ammonia emission leads to a minor increase in the sulphate concentration in precipitation. Under Danish conditions the relative contributions of various processes to the ammonium concentration in precipitation are in-cloud scavenging of ammonium aerosol 77%, below-cloud scavenging of ammonium aerosol 2%, in-cloud scavenging of ammonia 15% and below-cloud scavenging of ammonia 6%. The relative contributions of various processes to the nitrate concentration in precipitation are in-cloud scavenging of nitrate aerosol 91%, below-cloud scavenging of nitrate aerosol 2%, in-cloud scavenging of nitric acid 6% and below-cloud scavenging of nitric acid 1%. The relative contributions of various processes to the sulphate concentration in precipitation are in-cloud scavenging of sulphate aerosol 59%, below-cloud scavenging of sulphate aerosol 1%, in-cloud scavenging of sulphur dioxide 38% and below-cloud scavenging of sulphur dioxide 2%. It can be seen that, for the nitrogen and sulphur components, in-cloud scavenging of aerosols yields the largest contribution to the concentrations in precipitation. (AB)
Keywords: "54 ENVIRONMENTAL SCIENCES"; "ATMOSPHERIC CHEMISTRY"; "ATMOSPHERIC PRECIPITATIONS"; "DENMARK"; "AEROSOLS"; "AMMONIA"; "AMMONIUM COMPOUNDS"; "CLOUDS"; "COASTAL WATERS"; "DEPOSITION"; "NITRATES"; "NITRIC ACID"; "NITROGEN"; "UPTAKE"; "CHEMISTRY"; "COLLOIDS"; "DEVELOPED COUNTRIES"; "DISPERSIONS"; "ELEMENTS"; "EUROPE"; "HYDRIDES"; "HYDROGEN COMPOUNDS"; "INORGANIC ACIDS"; "NITROGEN COMPOUNDS"; "NITROGEN HYDRIDES"; "NONMETALS"; "OXYGEN COMPOUNDS"; "SCANDINAVIA"; "SOLS"; "SURFACE WATERS"; "WESTERN EUROPE"; "540320* - Environment, Aquatic- Chemicals Monitoring & Transport- (1990-)"; "540120 - Environment, Atmospheric- Chemicals Monitoring & Transport- (1990-)"